Biological Characteristics of Goldstripe Sardinella Sardinella gibbosa (Bleeker, 1849) in the Nearshore Area of Ham Thuan Nam District, Binh Thuan Province - Nam, Nguyen Thanh; Phuong, Ngo Anh; Huan, Nguyen Xuan (VNU Journal of Science: Natural Sciences and Technology, 2016)
Abstract: The biological analyses of 240 individuals of the Sardinella gibobosa collected in the nearshore area of Ham Thuan Nam district, Binh Thuan province in 2014 provided some important information: the total length of S. gibbosa ranged from 105 mm to 170 mm, with 134.71 mm on average, but mainly from 120 to 140 mm; and their weight ranged from 10 gr to 41 gr, with 20.90 gr on average and mainly in 10 gr - 20 gr (60.83%). The equation of relationship between total length (TL) and weight (W) for the whole stock is W = 0.6325 x L 2.7972 (R 2 = 0.8766). The fished stock included four age groups (0 + to 3 + ) but primarily in the 1 + age group (53.75%). The most predominant food item group was phytoplankton and crustaceans, which were found in the gut of most individuals examined. The first and the second degree of the stomach fullness made up significant proportions with 47.92% and 45.42%, respectively, while the third degree made up only a minor proportion (4.17%). The overall sex ratio (females to males) was 1.00 : 1.07. Sexual maturity of exploited fish individuals was essentially low, mainly at the stages I (42.08%) and II (47.92%). These data show that the goldstripe sardinella has been being overexploited, because exploiting fishes were mainly on young ones, which have not yet reached sexual maturity in the studied area. Keywords: Sardinella gibbosa , biological characteristics, growth equations, Binh Thuan, nearshore area.